Effect of Harvesting Age on Walking Ability, Pododermatitis, Carcass Percentage, Abdominal Fat Percentage, And Revenue/Cost Ratio of Broiler Chickens - Nursita, Ita Wahju; Putra, Donisius Adonara (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2024)
This study was conducted to evaluate the effect of harvesting age on walking ability, pododermatitis, carcass percentage, abdominal fat percentage, and revenue/cost (R/C) ratio in broiler chickens. Three groups of five thousand Cobb chickens were reared until slaughter at ages 21 days (T1), 28 days (T2), and 35 days (T3), specifically for animal welfare and carcass quality variables using a sample of 15 chickens. The different harvesting ages did not show a different effect on the ability to walk broiler chickens which was marked by the acquisition of a score of 0, namely the chickens walked normally without detectable abnormalities in all treatments. Different harvesting ages had a highly significant effect (P < 0.01) on pododermatitis, carcass percentage, and abdominal fat percentage of broiler chickens. Pododermatitis score of T1, T2, and T3 was 1.00 ± 0.00, 1.20 ± 0.45, and 2.40 ± 0.55, respectively. Carcass percentage of T1, T2, and T3 was 65.26 ± 3.30%, 71.30 ± 17.00%, and 76.54 ± 3.00%, respectively. Abdominal percentage of T1, T2, and T3 was 1.34 ± 0.05%, 1.58 ± 0.22%, and 2.18 ± 0.08%, respectively. As for the R/C ratio obtained by each treatment sequentially 1.06, 1.16, and 1,09 for T1, T2, and T3, respectively. It could be concluded that harvesting ages have an impact on several factors such as pododermatitis, carcass percentage, abdominal fat percentage, and R/C ratio, but have no impact on the walking ability of broiler. The highest score of R/C ratio is obtained by T2 which shows that the greatest profit is obtained in harvesting chickens aged 28 days.